Penentuan Awal Bulan Qomariyah dan Permasalahannya di Indonesia - Wahyu Widiana (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2010)
This paper answers the difference between hizab and rukyat system in Indonesia. When there is a difference, the public at large directly